Search for pair production of a new b′ quark that decays into a Z boson and a bottom quark with the ATLAS detector - Anduaga, Xabier Sebastián (2012)
A search is reported for the pair production of a new quark b′ with at least one b′ decaying to a Z boson and a bottom quark. The data, corresponding to 2.0fb-1 of integrated luminosity, were collected from pp collisions at √s=7TeV with the ATLAS detector at the CERN Large Hadron Collider. Using events with a b-tagged jet and a Z boson reconstructed from opposite-charge electrons, the mass distribution of large transverse momentum b′ candidates is tested for an enhancement. No evidence for a b′ signal is detected in the observed mass distribution, resulting in the exclusion at a 95% confidence level of b′ quarks with masses m b′<400GeV that decay entirely via b′→Z+b. In the case of a vectorlike singlet b′ mixing solely with the third standard model generation, masses mb′<358GeV are excluded.